Rights received by the victims of tortious deviant behaviour - Thuraisingam, Ambikai S.; Mohd Ishan, Zahira (Zes Rokman Resources, 2017)
The purpose of this study is to investigate the rights received by the victims of tortious deviant behavior in the workplace. It aims to explore the existing rights received by the victims of the tortious deviant behavior under the statutory measures. In this paper, we review the existing protection under the statute in three different jurisdictions surrounding the phenomenon of tortious deviant behavior at the workplace, paying particular attention to factors causes of such conduct. We will also provide an overview of the perplexing nature of such conduct and how countries like Australia and India extend protection under the law for affected victims. In Malaysia, there is no specific law which governs the provisions for conduct of tortious deviant behaviour in the workplace. This is a conceptual research paper which will address the statutory measures that have been employed in several private and public organisations. This study aims to analyse and determine whether the victims have received adequate protection and rights due to such conduct. Finally, due to inadequacy of empirical evidence and focus on assessment and treatment for victims are recognized in this paper, and several suggestions are made for future research and treatment avenues relating to the tortfeasors.